2019
DOI: 10.1093/ehjcr/ytz130
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac mucormycosis: a case report

Abstract: Background Mucormycosis is an invasive fungal infection (IFI) most commonly seen in immunocompromised patients. Diabetic ketoacidosis, haematopoietic transplantation, iron overload states, and deferoxamine therapy are considered to be some of the classical risk factors. While cutaneous and rhino-sinusoidal forms may be seen in immunocompetent (IC) individuals, cardiac and mediastinal involvement is rare. In this report, we describe a young patient without predisposing factors who presented as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…ROCM mucormycosis is the commonest form (45–74%), followed by cutaneous (10–31%), pulmonary (3–22%), renal (0.5–9%), gastrointestinal (2–8%), and disseminated infections (0.5–9%). Other unusual sites of infection reported in the literature from India are breast [ 44 ], ear [ 5 ], spine [ 45 , 46 ], heart [ 47 , 48 ], and bone infections [ 49 , 50 ]. Figure 2 describes the underlying disease and risk factors associated with clinical forms of mucormycosis.…”
Section: Clinical Forms Of Mucormycosismentioning
confidence: 99%
“…ROCM mucormycosis is the commonest form (45–74%), followed by cutaneous (10–31%), pulmonary (3–22%), renal (0.5–9%), gastrointestinal (2–8%), and disseminated infections (0.5–9%). Other unusual sites of infection reported in the literature from India are breast [ 44 ], ear [ 5 ], spine [ 45 , 46 ], heart [ 47 , 48 ], and bone infections [ 49 , 50 ]. Figure 2 describes the underlying disease and risk factors associated with clinical forms of mucormycosis.…”
Section: Clinical Forms Of Mucormycosismentioning
confidence: 99%
“…Mucormycosis is an IFI ordinarily seen in individuals with underlying predisposing risk factors including DM and hematological malignancies. Disseminated forms are usually seen in individuals with such risk factors, although rhino-sinusoidal and cutaneous forms may occur in all individuals [113].…”
Section: Mucormycosismentioning
confidence: 99%
“…Rhino-orbital-cerebral mucormycosis (ROCM) is involved in 50% of the infections, 18% infections are cutaneous, pulmonary mucormycosis contributes to 8% of the cases, 4% cases are related with gastrointestinal mucormycosis, disseminated infections are usually 3%, while 2% are renal infections (Jeong et al, n.d.; Prakash and Chakrabarti, 2021 ). Breast ( Kataria et al, 2016 ), ear ( Prakash et al, 2019 ), spine ( Hadgaonkar et al, 2015 , Shah and Nene, 2017 ), heart ( Bharadwaj et al, 2017 , Krishnappa et al, 2019 ), and bone infections ( Bhatt et al, 2018 , Urs et al, 2016 ) are some of the other less frequent sites of infection reported in India ( Prakash and Chakrabarti, 2021 ).
Fig.
…”
Section: Clinical Forms Of Black Fungusmentioning
confidence: 99%